Cuprous binding promotes interaction of copper transport protein hCTR1 with cell membranes. Issue 74 (28th August 2019) - Yang, Yang; Zhu, Yang; Hu, Hongze; Cheng, Lanjun; Liu, Manman; Ma, Guolin; Yuan, Siming; Cui, Peixin; Liu, Yangzhong
Abstract : Cu(i ) binding promotes the interaction of hCTR1 with cell membranes, which could initiate the cellular uptake of copper ions. Abstract : Cu(i ) binds to the N-terminal metal binding domain (MBD) of hCTR1 and induces its conformational change, which promotes the interaction of the MBD with cell membranes. The membrane interaction was confirmed in living cells. This process could be the first step to initiate the cellular uptake of copper ions by hCTR1.